N-TERMINAL PRO-BRAIN NATRIURETIC PEPTIDE IN DIAGNOSTICS OF NON-COMPACTED MYOCARDIUM IN CHILDREN - E. N. Arkhipova; I. V. Sil'nova; E. N. Basargina; I. V. Dvoryakovskii; A. B. Sugak; N. A. Mayanskii; M. K. Umarova (Union of pediatricians of Russia, 2012)
Non-compacted myocardium is a rare congenital cardiomyopathy. Due to the lack of uniform criteria, diagnostics of this condition is complicated presently, which results in over-diagnosing. N-terminal pro-brain natriuretic peptide (NT-proBNP) is a marker of chronic cardiac insufficiency (CCI) in children. The results of the study of NT-proBNP in non-compacted myocardium diagnostics are represented in this article. It was established, that serum NT-proBNP levels were higher in children with non-compacted myocardium than in children with CCI and without this disorder (р < 0,01). The received data can be useful in clinical practice.